2004
DOI: 10.1111/j.1744-7348.2004.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biotic and abiotic stress on the growth of three genotypes of Lolium perenne with and without infection by the fungal endophyte Neotyphodium lolii

Abstract: The combinations of three genotypes of Lolium perenne with and without (i) infection by the fungal endophyte Neotyphodium lolii, (ii) infection by ryegrass mosaic virus and (iii) one of five different forms of abiotic stress were studied in pot experiments in a glasshouse. The five abiotic stress treatments were (i) low pH (compared with 'optimal' pH), (ii) cutting plants to a height of 1 cm (compared with 5 cm), (iii) shading (compared with no shading), (iv) cutting plants at 2-weekly intervals (compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 25 publications
3
28
0
1
Order By: Relevance
“…Resource limitation can increase the cost of supporting some endophytes (Cheplick 2004;Müller and Krauss 2005), potentially leading to the interaction shift from mutualism to parasitism or commensalism (Marks and Clay 2007). In fact, many of the studies that have found improved growth in EI grasses were done under benign conditions of moderate to high soil nutrient availability (Cheplick et al 1989;Ravel et al 1999;Hesse et al 2003;Lewis 2004;Ren et al 2009). If enhanced drought resistance, combined with nitrogen (N) enrichment, is a common result of endophyte symbiosis, then increases in the severity and duration of drought could drive the replacement of EF grasses by EI hosts.…”
Section: Introductionmentioning
confidence: 96%
“…Resource limitation can increase the cost of supporting some endophytes (Cheplick 2004;Müller and Krauss 2005), potentially leading to the interaction shift from mutualism to parasitism or commensalism (Marks and Clay 2007). In fact, many of the studies that have found improved growth in EI grasses were done under benign conditions of moderate to high soil nutrient availability (Cheplick et al 1989;Ravel et al 1999;Hesse et al 2003;Lewis 2004;Ren et al 2009). If enhanced drought resistance, combined with nitrogen (N) enrichment, is a common result of endophyte symbiosis, then increases in the severity and duration of drought could drive the replacement of EF grasses by EI hosts.…”
Section: Introductionmentioning
confidence: 96%
“…First, relatively high infection frequencies have been observed in natural grass populations exhibiting little or no evidence that the fungus confers a reproductive advantage to its host (Saikkonen et al 1998;Faeth & Hamilton 2006). In fact, experimental evidence of a positive effect of endophytes on the fitness of their hosts has not been consistent (Cheplick et al 1989;Saikkonen et al 1998;Faeth 2002;Faeth & Sullivan 2003;Cheplick 2004;Lewis 2004;Faeth & Hamilton 2006); and modelling has demonstrated that local persistence of endophyte infection should be possible in the absence of such mutualistic effects, as a result of metapopulation dynamics (Saikkonen et al 2002). Second, natural populations often exhibit intermediate infection levels in contrast to modelling results showing that the frequency of infected plants in a population should equilibrate at 100% if the only driver was host fitness enhancement (Clay 1993;Ravel et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Belesky et al (1991) reported that the endophyte infection did not affect carbohydrate accumulation in tall fescue at low N supply; therefore, they thought that the endophyte infection was not detrimental to the host plant even under nutrient limited conditions. In perennial ryegrass, Lewis (2004) reported that EI grass used N more effectively than EF grass when grown at low N availability. Other studies with perennial ryegrass, however, showed minimal or inconsistent effects of endophyte at low N concentrations (Durand et al 2002).…”
mentioning
confidence: 99%
“…On one hand, the grasses provide photosynthates for the fungi; on the other hand, the endophytes can enhance the hosts' growth and protect them from biotic and abiotic stresses, contributing thus to their adaptability. Abiotic attributes affected by Neotyphodium endophytes include drought resistance (Hesse et al 2003), light stress (Lewis 2004), high temperature (Marks and Clay 1996), mineral stress, etc. Studies on endophyte-related responses of grasses to nutrient acquisition focused on the influence of nitrogen, since this element is a constituent of alkaloids in infected plants.…”
mentioning
confidence: 99%